ASCP Board of Certification Survey of Medical Laboratory Science education 2023: faculty. - Duzan, Dana; Fong, Karen; Freeman, Vicki S; Goodyear, Nancy; Nadder, Teresa S; Siddon, Alexa; Spiczka, Amy; Taff, Teresa; Tanabe, Patricia (Laboratory Medicine, 2026)
Introduction The American Society for Clinical Pathology Board of Certification Research and Development Committee has undertaken regular surveys of Medical Laboratory Science (MLS) education programs to gather information to support MLS program directors and faculty in educating students. Methods The survey was sent out to MLS program directors and faculty who answered questions related to demographics, education level and rank, certification patterns, experience, responsibilities, salaries, and retirement. Results Results were mainly analyzed by the respondents' titles. The survey data reveal a newer cohort of program directors and faculty, which affected data such as retirement and experience. Hospital program directors' and faculty's salaries have increased at a similar rate to inflation since 2020, but salaries for university program directors and faculty have increased at a much slower rate than inflation within the same time frame. Discussion Results of previous surveys in 2019 and 2022 are also reported. At the time the 2023 survey was conducted, laboratory professional training programs were beginning to return to the "new" normal following the COVID-19 pandemic restrictions. The results of this survey and those of subsequent years will shed light on the changes in the MLS education field and the impact of the pandemic on program directors and faculty.